Optimalisasi Strategi Penyampaian Materi Konsep Dalam Pembelajaran PAI Di MIN 2 Kabupaten Gorontalo - Muthmainah Putri Bolilio; Wanti S Lumuan; Regina Bilatula (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Institut Agama Islam YAPTIP Chadijah Ismail Pasaman Barat, 2024)
This article aims to explore optimal strategies for conveying conceptual material in Islamic Religious Education (PAI) learning. Understanding concepts is at the core of effective learning in the context of religious education, however, challenges arise in delivering material that is interesting to students. Through literature analysis and empirical research, this article identifies strategies that can improve the delivery of concept material in PAI. Strategies include understanding student characteristics to adapt learning methods, such as the use of visual media and interactive approaches. The use of information and communication technology is also emphasized, including digital learning applications and online platforms. It is hoped that the integration of this strategy can optimize learning of PAI concepts, increase student understanding and involvement. In conclusion, this article provides a holistic view of optimizing strategies for delivering conceptual material in PAI learning, for the advancement of quality religious education.